2015
DOI: 10.28945/2254
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Computer Simulation to Compare Student performance in Traditional versus Distance Learning Environments

Abstract: Simulations have been shown to be an effective tool in traditional learning environments; however, as distance learning grows in popularity, the need to examine simulation effectiveness in this environment has become paramount. A casual-comparative design was chosen for this study to determine whether students using a computer-based instructional simulation in hybrid and fully online environments learned better than traditional classroom learners. The study spans a period of 6 years beginning fall 2008 through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“… 27 In support of this a study done by Guy et al concluded that online simulations or virtual classes seem to be most effective when they are used complementary to conventional lectures which support better effective learning. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 In support of this a study done by Guy et al concluded that online simulations or virtual classes seem to be most effective when they are used complementary to conventional lectures which support better effective learning. 9 …”
Section: Discussionmentioning
confidence: 99%
“…6,8 In view of the pandemic situation, online teaching is justifiable but its usefulness in teaching medical and nursing courses is questionable as assessing student satisfaction with webbased learning systems has been a critical issue for researchers and academia. [9][10][11][12][13][14] The literature shows varied results regarding the satisfaction of students with online or web-based learning. 10,11 A few studies reported insecurities among the students and dropouts from the courses with online learning.…”
Section: Introductionmentioning
confidence: 99%
“…By using this online method as a transient solution to continue education, it seems to be acceptable to many people ( Chiu et al, 2005 , Geis et al, 1986 , Guy and Lownes-Jackson, 2015 , Roach and Lemasters, 2006 , Strong, 2012 , Sweet, 1986 ). Opinions about virtual teaching have been and still are controversial ( Chiu et al, 2005 , Sweet, 1986 ).…”
Section: Introductionmentioning
confidence: 99%
“…For much of the literature has stressed the increased levels of cognitive learning, it has the power to recreate complex, dynamic political Processes in the lecture, allowing students to examine the motivations, behavioral Constraints, resources and interactions among institutional actors. [25] Nowadays simulation is taking an important place in training and education of healthcare professionals. Simulations have been shown to be an effective tool in traditional learning environments.…”
Section: Discussionmentioning
confidence: 99%